First record of the nonindigenous Penaeus monodon Fabricius, 1798 (Penaeidae) in the Caribbean Sea of Costa Rica, Central America, with observations on selected aspects of its reproductive biology - Alfaro-Montoya, Jorge (2015)
This contribution reports, for the first time, the presence of the giant tiger shrimp Penaeus monodon Fabricius, 1798 on the northern Caribbean coast of Costa Rica. This closed-thelycum penaeid species is originally from the Indo-West Pacific, and it has been reported from other regions of the Western Central Atlantic; however, the reproductive biology of this species has not been examined in its non-native range. Adult females and adult males were captured by local fishermen near the Colorado River mouth during September and October 2014; animals were preserved in ethanol for further identification, and an evaluation of reproductive condition was conducted based on visual and histological staging of ovaries. Terminal ampoules of males were analyzed histologically to document spermatogenic activity. The specimens examined exhibited ovarian maturation, spermatophore production, and evidence of successful mating. The presence of this species can affect food chains and disturb ecosystem function and structure and locations where it is not native, which can, in turn, threaten ecosystem services to people dependent on this ecosystem for their livelihood.